Intradural Hemangiopericytoma of the Lumbar Spine: A Rare Entity - Fitzpatrick, D.; Mahajan, J.; Lewkowitz, M.; Black, K.; Setton, A.; Woldenberg, R. (American Journal of Neuroradiology, 2009)
SUMMARY: We report a case of a patient with an intradural hemangiopericytoma of the lumbar spine and the unusual MR angiography (MRA) and spinal angiography findings of arteriovenous shunting with spinal venous congestion. We highlight the concordance of the unusual MRA and angiographic findings and their relationship to combined endovascular and surgical therapy.